2022
DOI: 10.1371/journal.pone.0272997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of trace calls by Xpert MTB/RIF ultra for clinical management in low TB burden settings

Abstract: Background Clinical interpretation of trace results by Xpert MTB/RIF Ultra assay (Ultra) used as an initial diagnostic test for tuberculosis (TB) may be challenging. The aim of the study was to evaluate the frequency and epidemiology of trace readouts in routine clinical practice in a low TB prevalence setting and to propose guidance on how to manage patients with trace calls considering the data available (clinical, radiological, bacteriological etc.). Materials and methods A retrospective, observational, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The relatively high percentage of positive cultures in our series compared to that of Amedeo (71.7% versus 54.5%, respectively), may be due to the lower percentage of lymph node TB (55.9% versus 25%, respectively), that can remain sterile in culture. Severe neuromeningeal, digestive, and bone forms are paradoxically more often documented by culture in our study [9].…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…The relatively high percentage of positive cultures in our series compared to that of Amedeo (71.7% versus 54.5%, respectively), may be due to the lower percentage of lymph node TB (55.9% versus 25%, respectively), that can remain sterile in culture. Severe neuromeningeal, digestive, and bone forms are paradoxically more often documented by culture in our study [9].…”
Section: Discussionmentioning
confidence: 43%
“…Mazzola et al concluded that false positives results could be easily avoided by not performing the Ultra test on samples from patients with a clinically excluded diagnosis of TB or with a history of TB within 5 years [8]. According to Amedeo's study, trace results in presumptive TB patients should be considered as true positives and treatment should be started promptly, except in cases of recent TB [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because Ultra can detect MTB at “trace” levels, this feature can be helpful in establishing TB diagnoses in paucibacillary conditions. Studies have shown that the “trace” calls result in the early diagnosis of TB in smear-negative, culture-positive paucibacillary situations, leading to prompt treatments [ 25 , 26 ]. This highlights the significant clinical impact of Ultra’s “trace” feature in critical situations where the diagnosis could have been missed or delayed otherwise.…”
Section: Discussionmentioning
confidence: 99%